Diaquabis(2-bromobenzoato-κO)bis(N,N-diethylnicotinamide-κN (1))zinc(II) - Hökelek, Tuncer (International Union of Crystallography, 2009)
In the centrosymmetric title complex, [Zn(C(7)H(4)BrO(2))(2)(C(10)H(14)N(2)O)(2)(H(2)O)(2)], the Zn(II) atom is located on an inversion center. The asymmetric unit contains one 2-bromobenzoate (BB), one diethylnicotinamide (DENA) ligand and one coordinating water molecule. The four O atoms in the equatorial plane around the Zn atom form a slightly distorted square-planar arrangement, while the slightly distorted octahedral coordination is completed by the two N atoms of the DENA ligands in the axial positions. The dihedral angle between the carboxyl group and the adjacent benzene ring is 85.51 (12)°, while the pyridine and benzene rings are oriented at a dihedral angle of 44.07 (6)°. In the crystal structure, O—H⋯O hydrogen bonds link the molecules into infinite chains.